Structural behaviour and resistances of high strength concrete-filled stainless steel tube (HCFSST) beam-columns - Zhong, Yukai (2024)
This paper reports experimental and numerical investigations into the structural behaviour and resistances of high strength concrete-filled stainless steel tube (HCFSST) beam-columns under combined compression and bending. An experimental investigation was conducted on sixteen HCFSST beam-columns specimens fabricated from stainless steel tubes with two cross-section sizes and high strength concretes with four material grades, and included concrete cylinder tests, tensile coupon tests, initial global geometric imperfection measurements and eccentric compression tests. The test setups and procedures were fully reported and the experimental observations were discussed and analysed in detail. It was found that the plane cross-section assumption was valid for eccentrically loaded HCFSST sections and the lateral deflection distribution patterns for HCFSST beam-columns were approximately half-sine wave shapes. The test results were used in a subsequent numerical investigation for the validation of finite element models, which were then employed to conduct parametric studies to generate additional numerical data over a wide range of cross-section dimensions, member lengths and loading combinations. Based on the experimental and numerical results, the relevant design rules, as set out in the European code, American specification and Australian/New Zealand standard, were evaluated for their applicability to HCFSST beam-columns. The evaluation results revealed that the European code provided accurate but scattered failure load predictions when used for HCFSST beam-columns, while the American specification and Australian/New Zealand standard resulted in conservative and scattered failure load predictions.